Anti-beta 2 glycoprotein I IgA in the SLICC classification criteria dataset. (July 2021) - Elkhalifa, Marwa; Orbai, Ana-Maria; Magder, Laurence S; Petri, Michelle; Alarcón, Graciela S; Gordon, Caroline; Merrill, Joan; Fortin, Paul R; Bruce, Ian N; Isenberg, David; Wallace, Daniel; Nived, Ola; et al.
Objective: Anti-beta 2 glycoprotein I IgA is a common isotype of anti-beta 2 glycoprotein I in SLE. Anti-beta 2 glycoprotein I was not included in the American College of Rheumatology (ACR) SLE classification criteria, but was included in the Systemic Lupus International Collaborating Clinics (SLICC) criteria. We aimed to evaluate the prevalence of anti-beta 2-glycoprotein I IgA in SLE versus other rheumatic diseases. In addition, we examined the association between anti-beta 2 glycoprotein I IgA and disease manifestations in SLE. Methods: The dataset consisted of 1384 patients, 657 with a consensus physician diagnosis of SLE and 727 controls with other rheumatic diseases. Anti-beta 2 glycoprotein I isotypes were measured by ELISA. Patients with a consensus diagnosis of SLE were compared to controls with respect to presence of anti-beta 2 glycoprotein I. Among patients with SLE, we assessed the association between anti-beta 2 glycoprotein I IgA and clinical manifestations. Results: The prevalence of anti-beta 2 glycoprotein I IgA was 14% in SLE patients and 7% in rheumatic disease controls (odds ratio, OR 2.3, 95% CI: 1.6, 3.3). It was more common in SLE patients who were younger patients and of African descent (p = 0.019). Eleven percent of SLE patients had anti-beta 2 glycoprotein I IgA alone (no anti-beta 2 glycoprotein I IgG or IgM). There was a significant association between anti-beta 2 glycoprotein I IgA and anti-dsDNA (p = 0.001) and the other antiphospholipid antibodies (p = 0.0004). There was no significant correlation of anti-beta 2 glycoprotein I IgA with any of the other ACR or SLICC clinical criteria for SLE. Those with anti-beta 2 glycoprotein I IgA tended to have a history of thrombosis (12% vs 6%, p = 0.071), but the difference was not statistically significant. Conclusion: We found the anti-beta 2 glycoprotein I IgA isotype to be more common in patients with SLE and in particular, with African descent. It could occur alone without other isotypes.